Mimetic nanoparticles regulate the inflammation of ischemic myocardium. (25th November 2020) - Chen, J; Huang, Z.Y; Ge, J.B
Abstract: Background: Most drug delivery systems are lack of accurate targets, so the poor efficiency significantly limited the therapeutic effects. Neutrophil plays an important role in the acute phase of myocardial infarction. There are multiple chemokine receptors on the surface of cell membrane proteins, which participate in inflammatory chemotaxis and immune regulation. Purpose: Through syntheses and target delivery of biomimetic neutrophil liposomes (Neu-Lipos), it is possible to increase the delivery efficiency, reduce inflammation of ischemic region and promote the progression of myocardium repair. Methods and results: Biomimetic nanoparticles (Neu-Lipos) were synthesized using membrane proteins purified from activated neutrophils. Neu-Lipos were characterized using dynamic light scattering and were found to have a diameter of 163.5±3.6 nm, a surface charge of −28.7±1.6 mV. For in vivo studies, C57 mice were constructed of ischemia-reperfusion model. Mice were injected with either PBS, Lipos (5 mg/kg), or Neu-Lipos (5 mg/kg) one day after reperfusion. The targeting ability of Neu-Lipos to injured myocardium was significantly higher than Lipos. In mice treated with Neu-Lipo, the result of immunofluorescence revealed fewer M1 and more M2 infiltrating in border region compared with untreated mice and Lipo treated mice. Furthermore, macrophage polarization correlated with downward trends Inflammatory chemokines. Neu-Lipos–treated mice also displayed significantly decreased IL-1α, IL-1β and IL-6 in the injured myocardium. Histological analysis showed no significant toxicological alterations displayed in lung, spleen, kidney, or liver in Neu-Lipos treated group. Conclusions: We showed that our Neu-Lipos showed a decrease in proliferating macrophage population that was accompanied by the reduction of key proinflammatory cytokines and changes in myocardial repair. This proof of concept showed that our platform was capable of altering macrophage polariton within the injured tissue after treated and with a favorable toxicity profile. This treatment could be a promising intervention for the acute ischemia of myocardium. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The National Natural Science Foundation of China